Optimizing corrosion resistance of the Mg–4Zn-0.5Y-0.5Nd alloy by regulation of secondary phase and grain structure - C.C. Zhao; W.T. Ouyang; M. Wen; C. Yang; D.K. Xu; Y.F. Zheng; T.F. Xi; L.Y. Sheng (Journal of Materials Research and Technology)
The Mg–4Zn-0.5Y-0.5Nd alloy was designed and fabricated using conventional casting and subsequently heat treatment to optimize its microstructure and corrosion properties. The effects of secondary phase morphology and grain structure on the in vitro corrosion behavior of the alloy were systematically investigated to elucidate the corresponding mechanisms. The results show that the T4 treatment coarsens the equiaxed grains and transforms the secondary phase into thin cell skeleton structure with a slight decrease in area fraction. While the T6 treatment reconstructs the secondary phase into bulk ones along the grain boundary and fine ones inside the grain. The T4 treatment changes the corrosion potential and current density of the alloy obviously, but these values are changed by the T6 treatment a little. The As–C alloy has the highest corrosion rate of 0.91 mg cm−2 d−1, while the T4 alloy with solid solution treatment decreases to 0.65 mg cm−2 d−1, and the T6 alloy has a middle value between them. Such a corrosion behavior should be mainly ascribed to the evolution of secondary phase morphology and distribution caused by heat treatment. The Mg–Zn–Y-Nd alloys with different states all experience passivation, pitting corrosion, galvanic corrosion, localized corrosion, and extensive corrosion stages, but the duration time of different stages of different alloys differs obviously, which is mainly determined by the secondary phase morphology. Comparatively, the secondary phase with thin cell skeleton structure contributes to corrosion resistance, while the isolated bulk secondary phase accelerates the corrosion. Moreover, the appropriate coarsened grain structure is also beneficial to corrosion resistance.